Pengaruh Faktor Ekonomi Makro dan Kinerja Keuangan terhadap Nilai Perusahaan (Universitas Negeri Semarang, 2015)
The aim of this research is to know the effect of macroeconomics factors and financial performance on corporate value of the manufacturing companies in Indonesia Stock Exchange on 2010-2012. Population in this research is manufacturing companies listed on Indonesia Stock Exchange in the period from 2010 until 2012. Number of sample that used in this research is 52 samples with purposive sampling method. Corporate value variable is proxied by Price Earning Ratio (PER), macroeconomics factors variable is proxied by inflation and exchanges rate, financial performance variable is proxied by Return on Equity (ROE) and Debt to Equity Ratio (DER). The analytical tool used is multiple regression analysis, using software SPSS 16.0. Based on the results of the study, it can be concluded that only DER has significant effect on corporate value of manufacturing companies in IDX on 2010-2012.